2021
DOI: 10.3390/ijerph18031215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Its Associated Risk Factors in a Rural Black Population of Mthatha Town, South Africa

Abstract: Background: The occurrence of hypertension has been increasing alarmingly in both low and middle-income countries. Despite acknowledging hypertension as the most common life-threatening risk factor for cardiovascular disease (CVD), a dearth of data is available on the prevalence, awareness, and determinants of hypertension in rural parts of South Africa. The principal aim of the current study is to determine the prevalence and associated risk factors of hypertension among a black rural African population from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 103 publications
5
23
2
Order By: Relevance
“…Nevertheless, this finding is unexpected and further work is needed to validate the association identified in this study since these are in contrast with other reports from rural India [ 34 ] and Nigerian [ 35 ] which identify a higher BMI as a major risk factor for hypertension [ 18 , 36 , 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, this finding is unexpected and further work is needed to validate the association identified in this study since these are in contrast with other reports from rural India [ 34 ] and Nigerian [ 35 ] which identify a higher BMI as a major risk factor for hypertension [ 18 , 36 , 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We did not quantify the health and economic costs associated with hypertension in privately insured individuals. Previous studies have shown that income is not a significant predictor of elevated BP in South Africa, but it is a major determinant of hypertension awareness, treatment and control 4 56. Higher income individuals, including those with private health insurance, are more likely to receive treatment and are more likely to be employed.…”
Section: Discussionmentioning
confidence: 97%
“…(14) More than a quarter of the global adult population has hypertension and this percentage is expected to increase in the coming years in all regions, particularly in SSA. (15) Prevalence of hypertension in SSA is approximately 30%. (16) There were approximately 80 million patients with hypertension in SSA in 2000, and projections based on current epidemiologic data suggest that this figure will rise to over 150 million by 2025.…”
Section: Hypertensionmentioning
confidence: 99%